Clinical presentation and outcomes of anomalous left coronary artery from the pulmonary artery: a retrospective study from January 1998 - August 2019 at the Department of Paediatrics Cardiology, Universitas Hospital - Makhoba, Ntombikayise Gladys (University of the Free State, 2020)
BACKGROUND: Anomalous left coronary artery from the pulmonary artery (ALCAPA) or Bland-White-Garland syndrome is a rare congenital anomaly that has profound effects on heart function. Patients with ALCAPA present with non-specific symptoms like irritability, feeding difficulties and signs and symptoms of cardiac failure. If left untreated, ALCAPA has a 90% mortality rate in the first year of life, primarily due to myocardial ischemia and heart failure. It is therefore important to diagnose them in time and offer surgery. OBJECTIVES: The primary objective of the study was to determine the clinical presentation and severity of symptoms using the Ross classification and to describe the clinical status of the patients at last follow up, including the clinical outcome (Ross classification) and survival. METHODS: This was a retrospective descriptive study at the Department of Pediatric Cardiology between January 1998 and August 2019. All patients with the diagnosis of ALCAPA during the study period were included. Medical records of patients referred from Free State, Northern Cape and Lesotho were reviewed. Data collection included demographics of patients, clinical presentations, referral diagnosis, echocardiography before and after surgery, catheterization data, surgical data, clinical presentation at last follow up and ECHO at last follow up. Data was captured using the REDCap® online database. The researchers considered a Ross classification of more than two as clinically diagnostic of heart failure. The SF ranges were classified as follows: SF >28% = normal, SF 20-25% = mild, SF 15-20% = moderate and SF <15% =severe. RESULTS: During the study period a total of 30 patients presented to Universitas Paediatric Cardiology Unit with the diagnosis of ALCAPA. At presentation, 89% (n=25) of patients were in cardiac failure with a Ross classification for age of more than two. The diagnosis of ALCAPA was made primarily by echocardiography in 75.8% (n=22) of patients. Most patients 83.3% (n=25) had a dilated heart at presentation, with a median LVEDD z-score of 6.4 and 37% (n=11) had severe LV dysfunction (SF <15%). About half of the patients, 43% (n=13) had severe MR. ALCAPA repair was done in 76.6% (n=23) of our patients. The median age at surgery was 35 months (range: 1 day - 73 months), with a median weight of 6kg (range: 4kg - 20kg). The median days from diagnosis to the day of surgery was 11 days (range: 1 day to 6 years). Most patients had re-implantation of the anomalous left coronary artery except for two where the left coronary artery was tied off. One child required a left ventricular assist device (LVAD) for 7 days post operatively and survived. Immediately post-surgery there was some improvement on left ventricular function with 17% (n=4) of patients demonstrating normal SF and 13% (n=3) had mild left ventricular dysfunction. Heart failure symptoms (Ross) at follow-up improved significantly from original presentation (p < 0,01): forty five percent, (n=8) of our patients had no symptoms of cardiac failure, with Ross classification of two and less. At last follow a marked improvement on LV function was observed with 73% (n=11) patients having a normal SF. SF at last follow up showed a statistically significant difference compared to, at presentation with a p-value of 0.014. Seventy eight percent (n=18) of patients were alive at the end of the study and mortality post-surgery was 22% (n=5). CONCLUSION: Our results show that most children in central South Africa present in the first year of life with clinical features of heart failure. The most common echocardiographic features at presentation are impaired systolic function, dilated left ventricles and mitral regurgitation. Furthermore, surgery results in significant clinical and echocardiographic improvement. It is of paramount importance to have a high index of suspicion based on the clinical presentation and ECHO to ensure early referral, so corrective surgery may be offered timeously.
Dissertation (M.Med. (Paediatrics and Child Health))--University of the Free State, 2020
Keywords: Anomalous left coronary artery from the pulmonary artery; Ross classification; ECHO; Cardiac failure; Mitral regurgitation